Guidelines for chest drain insertion may not prevent damage to abdominal viscera. Issue 8 (21st November 2014) - Bowness, J; Kilgour, P M; Whiten, S; Parkin, I; Mooney, J; Driscoll, P
Abstract : Objectives: Guidelines to improve the ease and safety of chest drain insertion recommend using the fifth intercostal space, around the midaxillary line (MAL). This study aimed to assess whether compliance with published guidelines reliably ensured such placement and avoided the potentially serious complications of subdiaphragmatic insertion and peripheral nerve injury. Methods: Three international guidelines were assessed by identifying the intercostal space for chest drain insertion using 16 cadavers (32 sides) at a point 1 cm anterior to MAL. The European Trauma Course method was compared with the British Thoracic Society's 'safe triangle' and the ATLS course technique. Results: The level most commonly found was the sixth intercostal space (43%; 41 of 96 sides). Overall the sixth space or below was found in 83% of insertions (80 of 96 sides). In the fifth intercostal space, the long thoracic nerve ran posterior to the marker placed in all cases and the lateral cutaneous branches of intercostal nerves arose anteriorly to the marker in all but one case. Conclusions: The results suggest these guidelines may result in insertion of chest drains below the fifth intercostal space, potentially risking injury to subdiaphragmatic structures. Peripheral nerves of the lateral thoracic wall appear safe from incisions 1 cm anterior to MAL.